Continuation of proceedings when either party is a bankrupt: with reference to unfair dismissal claims in Industrial Court - Ali Mohamed, Ashgar Ali (LexisNexis Malaysia Sdn Bhd, 2009)
A claimant who alleged that his dismissal from employment was without just cause or excuse, the claimant must file his representation in writing in the Industrial Relation Department. The claimant's cause of action is that he considers his dismissal from employment was without just cause or excuse. The claim for dismissal without just cause or excuse is personal to the claimant.